Comparative study on the knowledge and use of plant biodiversity in the District of Mimoso (Santo Antônio de Leverger), Mato Grosso, Brazil - Pantanal Biosphere Reserve (Research, Society and Development, 2022)
The study was carried out with residents of the Mimoso Community, in the municipality of Santo Antônio de Leverger, Mato Grosso, with the objective of investigating ethnobotanical knowledge and comparing the use of plants from the morraria macrohabitat between the years 2000 and 2020. In 2000, they were interviewed 30 people, chosen at random and in 2020 29 people participated, selected through the snowball method. Information was collected through semi-structured interviews. In 2000, the interlocutors cited 91 ethnospecies and in 2020, they cited 83, of which 56 are shared in the two studies. The categories of uses with the highest number of citations were, respectively, in 2000 and 2020, distributed as follows: medicinal 49 and 42, construction 41 and 46 and utensil 36 and 26. Although the numerical difference between the two periods was not significant the similarity in the use of ethnospecies was low (4%). This result can be explained by the substitution of products found in the current local commerce for food and medicinal plants, the decrease of some individuals in the flora of the hills and the prohibition of their exploitation for timber species. Traditional knowledge about the use of plants is at risk due to the decrease in its use because what was commonly used may no longer be in future generations, and for the transmission of knowledge to occur, practices of daily use are necessary.